Epidemiology of intestinal parasite infections and multiparasitism and their impact on growth and hemoglobin levels during childhood in tropical Ecuador: A longitudinal study using molecular detection methods. - Rojelio Mejia; Irina Chis Ster; Martha E Chico; Irene Guadalupe; Andrea Arévalo-Cortés; Andrea Lopez; Aida Y Oviedo-Vera; Philip J Cooper (PLoS Neglected Tropical Diseases)
Background There are few longitudinal epidemiological studies of intestinal parasitic infections (IPI) and their health effects. We studied the epidemiology and determinants of IPI and multiparasitism during childhood using molecular methods for parasite detection and analysed their effects on growth and hemoglobin levels. Methods Random sample of 401 children from an Ecuadorian birth cohort followed up to 8 years of age. Data on environmental and sociodemographic characteristics were collected by questionnaires. Stool samples were collected, and weight, height, and hemoglobin levels were measured at 7 and 13 months, and 2, 3, 5, and 8 years. Stool samples were analysed using multi-parallel quantitative polymerase chain reaction for the presence of soil-transmitted helminth (STH) (Ascaris lumbricoides, Trichuris trichiura, Ancylostoma spp. Necator americanus, and Strongyloides stercoralis) and protozoal (Giardia lamblia, Entamoeba histolytica, and Cryptosporidium spp.) parasites. Associations between risk factors and infections, and between infections and nutritional outcomes were estimated using generalized estimated equations applied to longitudinal binary or continuous outcomes. Results IPI were observed in 91.3% of the cohort during follow-up with peak proportions between 3 and 8 years, while multiparasitism increased more gradually (32.5% at 8 years). Factors significantly associated with multiparasitism included lower birth order, day care, Afro-Ecuadorian ethnicity, urban residence, lower household income, and maternal STH infections. IPI during follow-up were associated with lower hemoglobin (difference = -0.102, 95% CI -0.192 - -0.013, P = 0.025), height-for-age (difference = -0.126, 95% CI -0.233 - -0.019, P = 0.021) and weight-for-age (difference, -0.129, 95% CI -0.257 - -0.022, P = 0.018) z scores. Multiparasitism had the strongest negative effects on growth (height-for-age, -0.289, 95% CI -0.441- -0.137, P < 0.001; weight-for-age, -0.228, 95% CI -0.379 - -0.077, P = 0.003), with some evidence of greater effects with greater number of parasite species. Conclusion IPI infections and multiparasitism were frequent during early childhood in this Ecuadorian cohort. IPI was associated with reduced weight, height, and hemoglobin trajectories while children with multiparasitism had the greatest growth deficits. Our data highlight the adverse health effects of multiparasitism during childhood in endemic settings and the need for integrated programmes of control and prevention to eliminate associated morbidity.